Ways Ahead: developing a supported self-management programme for people living with low- and intermediate-grade gliomas - a protocol for a multi-method study - Joanne Lewis; Vera Araujo-Soares; Pamela Gallagher; Sophie Williams; Tracy Finch; Ben Rimmer; Lizzie Dutton; Richéal Burns (BMJ Open)
Introduction Living with and beyond a diagnosis of a low- and intermediate-grade glioma (LIGG) can adversely impact many aspects of people’s lives and their quality of life (QoL). In people with chronic conditions, self-management can improve QoL. This is especially true if people are supported to self-manage. Supported self-management programmes have been developed for several cancers, but the unique challenges experienced by LIGG survivors mean these programmes may not be readily transferable to this group. The Ways Ahead study aims to address this gap by exploring the needs of LIGG survivors to develop a prototype for a supported self-management programme tailored to this group.Methods and analysis Ways Ahead will follow three sequential phases, underpinned by a systematic review of self-management interventions in cancer. In phase 1, qualitative methods will be used to explore and understand the issues faced by LIGG survivors, as well as the barriers and facilitators to self-management. Three sets of interviews will be conducted with LIGG survivors, their informal carers and professionals. Thematic analysis will be conducted with reference to the Theoretical Domains Framework and Normalisation Process Theory. Phase 2 will involve co-production workshops to generate ideas for the design of a supported self-management programme. Workshop outputs will be translated into a design specification for a prototype programme. Finally, phase 3 will involve a health economic assessment to examine the feasibility and benefits of incorporating the proposed programme into the current survivorship care pathway. This prototype will then be ready for testing in a subsequent trial.Ethics and dissemination The study has been reviewed and approved by an National Health Service Research Ethics Committee (REC ref: 20/WA/0118). The findings will be disseminated through peer-reviewed journals, conference presentations, broadcast media, the study website, The Brain Tumour Charity and stakeholder engagement activities.